How compassion can transform our politics, economy, and society - Hawkins, Matt; Nadel, Jennifer (Routledge, Taylor & Francis Group, 2022)
"How Compassion can Transform our Politics, Economy, and Society draws together experts across disciplines - ranging from psychology to climate science, philosophy to economics, history to business - to explore the power of compassion to transform politics, our society, and our economy. The book shows that compassion can be used as the basis of a new political, economic, and social philosophy as well as a practical tool to address climate breakdown, inequality, homelessness, and more. Crucially, it also provides a detailed plan for its execution. It marks the first time that the study of compassion has been applied across multiple disciplines. The book provides a template for the study of compassion on an interdisciplinary basis and will appeal to academics, professionals and the general reader searching for a fresh and inspiring approach to the seemingly intractable problems facing the world"--
Keywords: Mitgefühl; Sozialer Wandel; Compassion; Social ethics; Political ethics; Economics / Moral and ethical aspects